Analisis Meta Regresi untuk Menjelaskan Heterogenitas Hasil Penelitian pada Kejadian Demam Berdarah Dengue - S. Shindy; Muhammad Kasim Aidid; Muhammad Nusrang (Universitas Negeri Makassar, 2021)
Abstract. Meta regression analysis is an analysis that can summarize the results of research with the same topic so that a conclusion is obtained in the form of effect size and can explain the heterogeneity of the results of several studies. In this study using data from the previous Dengue Hemorrhagic Fever incident study which linked the factors of habit of draining habits of water shelters (TPA). Based on the results of the analysis, there was heterogeneity between studies. For the landfill drainage factor, the estimated parameter combined effect size random effect model is 3.60 and the proportion of heterogeneity is 54.08%. The results of the meta-regression for habitual factors of landfill drainage factors, the influence of TPA drainage habits can explain heterogeneity between effect sizes.Keywords: Effect size, Heterogeneity, Meta Regression Analysis, Dengue Hemorrhagic Fever.